VARIATIONS IN THE 87SR/86SR RATIO IN VOLCANIC GLASSES FROM THE DZHRABER EXTRUSION, ARMENIA - Shatagin K.N.; Volkov V.N.; Nasedkin V.V. (My University, 2004)
Variations in the initial Sr-87/Sr-86 ratio in volcanic glasses from the upper part of the Late Pleistocene Dzhraber Extrusion are discussed. Samples of obsidian and perlite formed by autometamorphic hydration of the primary glass were studied. Obsidian relics were sometimes separated from the partly perlitized breccia with obsidian replaced by perlite, and sometimes the samples were taken from vertical sections of the perlite cap occupying a considerable exposed part of the extrusion and from a vein-shaped obsidian body hosted in perlites. The study of perlite-obsidian breccia has shown that the perlitization gave rise to an increase in the Sr-87/Sr-86 ratio by 0.005-0.015% and to depletion in Rb and a respective decrease in the Rb-87/Sr-86 ratio. The Sr-87/Sr-86 ratio in vertical sections through the perlite and obsidian bodies is variable. The character of heterogeneity in both sections is similar, however, the Sr-87/Sr-86 value of perlite is systematically higher than obsidian sampled at the same hypsometric level. Hence, the fluid responsible for hydration of the primary glass contained Sr whose isotopic composition was different from that of the glass itself.